The Impact of Scarcity and Flash Sale Techniques on Impulse Buying of Cosmetics - Vera Rachmania; Muhammad Inzaghi Ramadhan; Siska Ernawati Fatimah (Journal of Management and Entrepreneurship Research, 2025)
Objective: This study examines the impulsive buying behaviour of cosmetic consumers on e-commerce platforms through the application of scarcity and flash sale techniques. Research Design & Methods: A total of 398 respondents from Cirebon City participated in this quantitative study, selected using an accidental sampling method. Data were collected through an online survey and analysed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Findings: Both scarcity and flash sale techniques influence impulse buying behaviour, with scarcity having the stronger effect. Flash sales stimulate urgency through limited-time offers, while scarcity enhances perceived value due to product limitation. Implications and Recommendations: Marketers are encouraged to combine flash sales and scarcity techniques to increase urgency and desirability. Brief, strategic discounts can effectively encourage unplanned purchases. Contribution & Value Added: This study provides valuable insights into e-commerce strategies that enhance impulse buying behaviour in the digital beauty sector.